The Evaluation of Community Participation and Sudin Fire Management and City Saving Administration Jakarta Utara in Fire Prevention in Kecamatan Tanjung Priuk Jakarta Utara - Lilik Mulyono; Ardani (IJESS International Journal of Education and Social Science, 2021)
This research is to determine the level of community participation in fire prevention management in Tanjung Priuk District, North Jakarta Administrative City. The theory used in this research is Arnsteint Theorie's which is quoted by M.Nuh which was the former minister of National Education, Susilo Bambang Yudhoyono era, it is an ideal theroy to determine the level of community participation. The research method is qualitative to obtain main data from interviewees. The description of the research is to get main data from valid interviewees who get envolve in prevention and fire management, also has been support by data of the field studies. Then analyze by triangulation process, to determine the level of community participation. The research indicates that the level of community participations in fire prevention in Tanjung Priuk District is informing, consulting and promising the programs to educate the community on fire and fire exhinguish drill, as well it will be an annual year. In the management process, the community is in the sevent step of the second level because the community has been the partners of the fire fighter in the scene. The community can extinguish the fire in the initial stage of fire growth.